2016
DOI: 10.1002/hep.28812
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in the health care burden and mortality of acute on chronic liver failure in the United States

Abstract: Cirrhosis and ACLF represent a substantial and increasing health and economic burden in the United States; these data highlight an urgent need for research on pathophysiological mechanisms and effective therapy as well as for education of health care providers of its importance in the care of patients with cirrhosis. (Hepatology 2016;64:2165-2172).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
113
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 20 publications
6
113
2
3
Order By: Relevance
“…Our previous study of all admissions for cirrhosis in the country, which used the National Inpatient Sample database, suggested that there were 659,000 admissions for cirrhosis in the United States in 2011 11. If we apply the admission rate of 100 per 100,000 population for initial hospitalization for cirrhosis in Olmsted County, the number of initial hospitalizations for cirrhosis in the United States for 2011 is estimated to have been 310,000.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study of all admissions for cirrhosis in the country, which used the National Inpatient Sample database, suggested that there were 659,000 admissions for cirrhosis in the United States in 2011 11. If we apply the admission rate of 100 per 100,000 population for initial hospitalization for cirrhosis in Olmsted County, the number of initial hospitalizations for cirrhosis in the United States for 2011 is estimated to have been 310,000.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of cirrhosis is expected to steadily increase over the next decade and is likely to be driven by the rising prevalence of nonalcoholic fatty liver disease (NAFLD) and the downstream consequences of progressive liver disease due to nonalcoholic steatohepatitis (NASH) . The complications of cirrhosis have and will lead to more hospitalizations and acute‐on‐chronic liver failure (ACLF), which will increase the demand for liver transplantation (LT) . In addition, we expect to transplant older people with more chronic kidney disease (CKD) secondary to the decline in hepatitis B virus– and hepatitis C virus (HCV)–related advanced liver disease and a continued increase in the prevalence of NAFLD …”
mentioning
confidence: 99%
“…With an increased need for LT and the changes in the patient population listed for transplant, we expect more patients to need hospitalization before transplant . In addition, we anticipate ACLF will also continue to increase in incidence before LT. Current data have shown that transplant‐free survival is markedly reduced in patients who develop ACLF, regardless of the definition of ACLF used . This is also applicable to patients listed for LT who have a high mortality before LT once ACLF develops …”
mentioning
confidence: 99%
“…Liver failure remains a major challenge for physicians in liver centers and represents a marked health and economic burden in China and the United States [26,27]. The indications for artificial organ support and emergency liver transplantation in ACLF patients are poorly defined [28].…”
Section: Discussionmentioning
confidence: 99%